Otimização de um método extrativo a partir dos frutos de Pterodon pubescens BENTH. Com vistas a obtenção de extratos e formulações com atividade antileishmania - Santos, Everton da Silva (2017)
Currently, leishmaniasis is difficult to manage owing to the limited choice and high toxicity of available drugs, and emergence of drug-resistant protozoa. Medicinal brazilian plants, which produce various bioactive molecules, can help counter this global shortage antileishmanial. And extracting by supercritical fluid extractions is green intended to protect the environment by not using harmful organic solvents. In this study, we prepared Pterodon pubescens fruit extracts, which show antileishmanial activity, and developed a nanoemulsion of the optimized extract to improve its performance in order to improve the antileishmanial activity and decrease its cytotoxicity. The extracts were prepared using conventional methods (turboextraction and maceration) and a supercritical fluid method and were tested for activity against Leishmania amazonensis promastigotes and intracellular amastigotes. The two most effective extracts were formulated as nanoemulsions. Although both extracts showed cytotoxicity with CC50 of 35.3; 36.3 and 35.5 μg/mL for the turboextracted fraction, macerated and supercritical extract respectively, the supercritical extracts were more effective against L. amazonensis promastigotes and intracellular amastigotes with IC50 of 26.3 and 33.8 μg/mL, respectively, against 42 and 52.1 IC50 in promastigotes, with hexanicas fractions turboextracted and macerated. This was attributed to the high content of the geranylgeraniol derivative in the supercritical extracts. The nanoemulsions showed a better selectivity index and significantly improved activity against parasites (IC50: 2.7 μg/mL for nanoemulsion of hexane extract; IC50: 1.9 μg/mL for nanoemulsion of supercritical extract) compared to the miltefosine standard (0.7 μg/mL). This could be due to the smaller droplets of the supercritical extracts, allowing better penetration. In conclusion, the extracts and nanoemulsions proved promising in vitro tests. and in vivo studies are necessary. But puts the fruits of the species as possible alternative treatments against leishmaniasis.